(untitled) (Journal of Hama University, 2024)
The work aims to study the effect of adding different levels Of organic zinc and selenium to Broiler feed Mixtures on productive parametres. A total of 120 one-day-old hybrid Ross308 chicks were used. The chicks were randomly distributed into four groups, each group included thirty chicks, All groups were treated under the same conditions of heat and feeding except level Of organic zinc and selenium to Broiler feed Mixtures according to the research plan, as it included four treatments; the control group which was provided with feed according to American fodder needs (NRC, 1994) included on (50 gr zinc inorganic + 0.32 gr selenium inorganic) ton of feed. The other experimental groups were provided with organic zinc and selenium according at levels (333 gr zinc organic + 5 gr selenium organic) ton of feed, (500 gr zinc organic + 10 gr selenium organic) ton of feed, (700 gr zinc organic + 15 gr selenium organic) ton of feed. The results showed that addition organic zinc and selenium to broiler feed mixtures has led to a significant increase (P<0.05) in body weight, body weight gain and feed consumption, As well as a significant improvement in efficiency of feed conversion in all experimental groups to which different levels of organic zinc and selenium were added to their feed mixtures compared to the control group. which led to a better profit index for the birds of those groups. While the addition of organic zinc and selenium did not have any significant effect on the mortality rate. it is concluded that adding organic zinc and selenium has a positive effects on the productive Indicators and the economic viability of broiler chickens.